Apostoł Andrzej – osoba i imię - Hrynkiewicz-Adamskich, Bożena (Studia Rossica Posnaniensia, 2021)
In Christian religious consciousness, especially in Eastern Christianity, Andrew the Apostle has a place equal to that of his brother, Peter the Apostle. This article presents the information gathered about him and provided by the Gospel and the Acts of the Apostles. It also concisely describes the apocrypha about his missionary activities in Greece, Pontus, Thrace and Scythia, as well as the sources and reasons behind the development of his cult in Europe, including the Slavic nations. The origin of the given name Andrew is also included, along with the process of this name becoming common among the Slavs connected with the spread of the cult. The article stresses the importance of the transformation of the original image of this saint caused by the contamination of Christian beliefs and Slavic folk culture. The analysis of Polish calendar proverbs enabled to present the linguistic image of St. Andrew. Folk religious rites connected with his cult, which emerged as the result of intertwining of the Christian calendar and agricultural cycle, are also described. The saints to whom certain days in the Christian calendar were dedicated, started to be perceived as the guardians of these days, protecting people from the forces of nature, as well as the protectors of certain trades. The profiles of selected local Christian saints bearing the name Andrew are also presented.